Dairy Consumption and Body Mass Index Among Adults: Mendelian Randomization Analysis of 184802 Individuals from 25 Studies. (4th January 2020) - ,; Huang, Tao; Ding, Ming; Bergholdt Helle, K M; Wang, Tiange; Heianza, Yoriko; Sun, Dianjianyi; Frazier-Wood Alexis, C; Aslibekyan, Stella; North Kari, E; Voortman, Trudy; Graff, Mariaelisa; et al.
Abstract: BACKGROUND: Associations between dairy intake and body mass index (BMI) have been inconsistently observed in epidemiological studies, and the causal relationship remains ill defined. METHODS: We performed Mendelian randomization (MR) analysis using an established dairy intake-associated genetic polymorphism located upstream of the lactase gene ( LCT -13910 C/T, rs4988235) as an instrumental variable (IV). Linear regression models were fitted to analyze associations between ( a ) dairy intake and BMI, ( b ) rs4988235 and dairy intake, and ( c ) rs4988235 and BMI in each study. The causal effect of dairy intake on BMI was quantified by IV estimators among 184802 participants from 25 studies. RESULTS: Higher dairy intake was associated with higher BMI (β = 0.03 kg/m 2 per serving/day; 95% CI, 0.00–0.06; P = 0.04), whereas the LCT genotype with 1 or 2 T allele was significantly associated with 0.20 (95% CI, 0.14–0.25) serving/day higher dairy intake ( P = 3.15 × 10 −12 ) and 0.12 (95% CI, 0.06–0.17) kg/m 2 higher BMI ( P = 2.11 × 10 −5 ). MR analysis showed that the genetically determined higher dairy intake was significantly associated with higher BMI (β = 0.60 kg/m 2 per serving/day; 95% CI, 0.27–0.92; P = 3.0 × 10 −4 ). CONCLUSIONS: The present study provides strong evidence to support a causal effect of higher dairy intake on increased BMI among adults.